Analysis of the anxiety level and influencing factors during the coronavirus disease 2019 epidemic among the parents of students in China - Han, Jing; Zhang, Xi; Zhang, Shengchao; Li, Yuting; Zhang, Dongmei; Chen, Qingsong (Frontiers in Public Health, 2023)
Background: Due to the outbreak of Coronavirus Disease 2019 , there has been a significant impact on the mental health of parents.However, no detailed study on the mental health status of parents has been conducted to date. Methods: This study was a cross-sectional used a whole-group random sampling method to conduct an online questionnaire survey with 102,883 parents in Guangdong Province, China, April 25,2020 and May 14,2020. Anxiety was assessed by using the Generalized Anxiety Disorder tool (GAD-7). Potential factors of anxiety were estimated using univariate analysis and multivariate logistic regression analysis by SPSS 22.0 statistical software. Results: Among the total 9,4705 parents who have completed the questionnaire survey (92.05% response rate). The incidence of anxiety was 23.77%. Parents' anxiety symptoms are more likely to be caused by female family roles, higher levels of education, unemployed or jobless employment status, children not being an only child, and children having negative attitudes towards online courses. Conclusions: Our research shows that most parents experienced mild anxiety during the Coronavirus Disease 2019 epidemic. Our findings provide strong evidence for investigating and focusing on the mental health of this population during the COVID-19 epidemic.Therefore, governments and healthcare departments at all levels should actively provide psychological counseling services to relieve their anxiety symptoms.